Ensino de ciências por investigação: desafios e possibilidades para professores de ciências - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
Some Current researches demonstrate effectiveness of Science Teaching through research to provide significant gains in student learning in science classes. However, it is known that this approach is not usual in teachers' pedagogical practice and presents many challenges. So, this work aims to: i) identify and analyze Science teacher of Municipal Education School in Anápolis-Goiás in the implementation of science teaching by investigation in the school; Ii) develop a support material for teachers with suggestions of experimental investigative classes; Iii) to investigate the potential of the material produced, testing the application with the 7th grade Elementary School of the Municipal public school Network of Education of Anápolis-GO To reach the first objective, a questionnaire was applied with objective and discursive questions to the science teachers; For the second, a booklet was produced with experimental investigative activities to be developed in the classroom. In relation to the third, a case study was carried out, between May and June of 2016, with a participant researcher. To identify these challenges, instruments of data collection and recording were used: observation with annotations; Audio recording; semi structured interview with the regent teacher and with a group of 15 students. In addition, the students elaborated a text and constructed a conceptual map. It was possible to verify that the greatest difficulties pointed out by teachers to develop research teaching are: crowded rooms, lack of discipline, lack of knowledge of the approach and lack of training. Aware of this, the educational product can greatly assist teachers in using such an approach in the classroom. The booklet was titled as "Every Day is Science Day: Investigative Experiments" and will be distributed free to teachers of the municipality. The application of one of the classes was set up as a case study and showed the difficulty of some students in participating in the activity, in understanding the stages of the investigation, the difficulty in constructing the conceptual map and in understanding the meaning of the term hypothesis. Despite the difficulties encountered, there were positive points in this experimental approach. The production of the final text by the students brought new concepts, ideas and coherent arguments about classification. In addition, a valuable fact of the process was the moment of exposition and communication of the results made by the students. So, it is essential importance to promote the adequate training of teachers to promote the implementation of research teaching and thereby alleviate the challenges for both teachers and students in the development of research experiments in science classes. In addition, make available material and didactic resources with orientations of investigative activities.
Keywords: Produto educacional; Experimentos Investigativos; Educação Básica; Biologia; Educational product; Investigative Experiments; Basic education; Biology; EDUCACAO::ENSINO-APRENDIZAGEM